UPAYA PENINGKATAN PENGETAHUAN TENTANG TUMOR DAN KANKER BAGI PERAWAT DI RSIA CEMPAKA Az - ZAHRA BANDA ACEH - Putri Ilham Sari (CV SWA Anugerah, 2024)
Abstract The impact of non-communicable diseases, especially cancer, on human resource resilience is large because in addition to being a cause of death and illness, it also reduces productivity. The morbidity and mortality rates mostly occur in people with lower-middle socioeconomic levels. Cancer is a disease with multifactorial causes that forms over a long period of time and progresses through different stages. RSIA Cempaka Az - Zahra as the only Maternity and Child Hospital in Banda Aceh City, of course always be ready to accept patients with oncology cases. Health workers have an important role in providing care, motivation to cancer patients indirectly they can increase the potential for healing or improve the quality of life of cancer patients. There is still a lot of misunderstanding among health workers about the difference between tumors and cancer, which often leads to errors in providing information to patients which can result in reducing the motivation to recover and the psychology of patients. The socialization was carried out at RSIA Cempaka Az - Zahra Banda Aceh. The target group is all nurses working at RSIA Cempaka Az - Zahra. The implementation began with the provision of a pre-test to participants, followed by the provision of material about tumors and cancer and early cancer screening practices. Based on the evaluation, there was an increase in knowledge after being given material and practice, proven by 80% of participants being able to perform early cancer examinations correctly.